Level of Awareness of Breast Cancer Among Adult Female in a Tertiary Level Hospital - Kabir, Bipasha; Islam, Shapla; Gupta, Sourav Das (Bangladesh Armed Forces Medical Journal, 2024)
Background: Breast cancer is the leading and most prevalent form of cancer among the women in Bangladesh. The aim of the study was to assess the level of awareness of the breast cancer among adult female. Methods: A descriptive cross-sectional study was conducted among 103 adult females in Out Patient Departments (OPDs) of Combined Military Hospital (CMH), Dhaka during July to December 2013. Data were collected purposively by face-to-face interview with a semi-structured questionnaire. Results: A total of 103 adult females participated in the study with the mean (±SD) age was 36.26±12.70. Majority 39(37.9%) of the respondents were in age group 29-39. Most 82(79.6%) of the participants were married, 90(87.4%) were housewives, 31(30.1%) were HSC qualified. Maximum 31(88.35%) respondents had average knowledge on breast cancer. Education and occupational status was found significantly associated with level of knowledge of the respondents. Conclusion: The overall knowledge of the respondents was found average. As it is a major health burden in women and incidence is very high in Bangladesh concern authority should take necessary action to adopt measures to increase the awareness on breast cancer. Bangladesh Armed Forces Med J Vol 57 No (1) June 2024, pp 14-21